Evaluating the potential energy savings of retrofitting low-rise suburban dwellings towards the Passivhaus EnerPHit standard in a hot summer/cold winter region of China - Liu, Chenfei; Mohammadpourkarbasi, Haniyeh; Sharples, Steve (Energy and buildings, 2021)
This paper considers the potential heating and cooling energy savings from retrofitting to the Passivhaus EnerPHit standard a low-rise suburban dwelling in the southern Chinese town of Huilong, which has a hot summer/cold winter climate. An existing residential building in Huilong was chosen as a case study and a baseline digital model was created with the dynamic thermal simulation software DesignBuilder. The model was validated using 12 months of air temperature and relative humidity measurements from the building. The virtual retrofitting process of the baseline model involved insulating the envelope, improving the airtightness and adopting a high efficiency mechanical ventilation heat recovery system. It was more difficult to reach the EnerPHit cooling energy demand criterion than the heating target, and so additional passive cooling from shading and natural ventilation were adopted to finally achieve the EnerPHit standard. The final simulation results suggest that the EnerPHit standard for energy was successfully achieved, with a 90% heating energy demand reduction (down to 14.9 kWh/m2a), and a 70% cooling energy demand (down to 12.6 kWh/m2a), compared to the dwelling’s baseline values.